P–p orbital interaction via magnesium isovalent doping enhances optoelectronic properties of halide perovskites. Issue 100 (7th December 2020) - Qian, Feng; Gong, Jue; Hu, Mingyu; Ge, Chunyu; Padture, Nitin P.; Zhou, Yuanyuan; Feng, Jing
Abstract : p–p orbital interaction through Mg(ii ) isovalent doping in methylammonium lead chloride perovskite significantly enhances the electronic properties while not affecting the optical bandgap. Abstract : p–p orbital interaction through Mg(ii ) isovalent doping in methylammonium lead chloride perovskite significantly enhances the electronic properties while not affecting the optical bandgap. This chemical behaviour shows promising applications to optoelectronic devices.